2021
DOI: 10.1101/2021.01.03.425119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SERS uncovers the link between conformation of cytochromecheme and mitochondrial membrane potential

Abstract: Cytochrome c is an essential component of the electron transport chain (ETC), which regulates respiratory chain activity, oxygen consumption, and ATP synthesis. But the impact of conformational changes in cytochrome c on its function is not understood for lack of access to these changes in intact mitochondria. Here we describe a label-free tool that identifies conformational changes in cytochrome c heme and elucidates their function. We verify that molecule bond vibrations assessed by surface-enhanced Raman sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The first ratio, I 1638 /I 1375 , shows the probability of the planar heme conformation. The higher this ratio is, the higher the probability of a planar conformation of the heme is [ 33 , 34 ]. Moreover, the use of ratios of peak intensities causes the spectral analysis to be independent of the local SERS signal intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first ratio, I 1638 /I 1375 , shows the probability of the planar heme conformation. The higher this ratio is, the higher the probability of a planar conformation of the heme is [ 33 , 34 ]. Moreover, the use of ratios of peak intensities causes the spectral analysis to be independent of the local SERS signal intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Our results clearly indicate the absence of the effect of hypertension on the probability of the planar heme conformation ( Figure 3 b). The ratio of I 1175 /I 1375 peak intensities represents the probability of the asymmetric pyrrole half-ring vibrations and can be used as a marker of heme mobility: the higher this ratio is, the higher the in-plane mobility of the heme is [ 33 , 34 ]. We found that this ratio is more dispersed in erythrocytes than in erythrocyte ghosts ( Figure 3 c), which may be explained by the more heterogeneous Hb population in the submembrane region of intact erythrocytes than in erythrocyte ghosts ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…Silver nanoparticles (Ag-NPs) are widely used as a nanomaterial with superior plasmonic properties, and the SERS activity of Ag-NPs is shown and developed in a variety of studies [14][15][16][17][18][19]. The SERS phenomenon can also allow using such NPs in the solar energy conversion systems [20] and as biosensors for the detection of different substances both in water and in vitro [17,21]. Ag-NPs deposited on the HNTs surface can result in localized surface plasmon resonance (LSPR) in the region of 400 to 600 nm [11,22] and thus it could be used for SERS [3].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregates of silver nanoparticles [18] and composite silica-silver nanostructures made it possible to amplify the Raman signal at large distances from submembrane molecules inside intact mitochondria or erythrocytes [19]. Nanostructured silver surfaces were used for labelfree studies of conformational changes in cytochrome C heme in functional mitochondria adsorbed on its surface [20,21]. The SERS platform, consisting of graphene-coated gold nanopyramids, was used to study the intracellular composition, which made it possible to distinguish the p53 knockout cancer cell line [22].…”
Section: Introductionmentioning
confidence: 99%